Reverse Phenotyping Maternal Cystic Kidney Disease by Diagnosis in a Newborn: Case Report and Literature Review on Neonatal Cystic Kidney Diseases - Ruzgienė, Dovilė; Sutkevičiūtė, Meda; Burnytė, Birutė; Grigalionienė, Kristina; Jankauskienė, Augustina (Acta medica Lituanica, 2021)
Kidney cysts are the most common kidney lesion, while congenital kidney cysts are mostly found in pediatric population. Neonatal kidney cysts can develop due to fetal malformations, rare genetic disorders or can be acquired which is very rare. Kidney cysts may be the only isolated finding or be part of the overall phenotype. They can be asymptomatic, found by ultrasound accidentally or can manifest from mild to life-threatening symptoms. Therefore, early diagnosis is very important. Autosomal dominant polycystic kidney disease and autosomal recessive polycystic kidney disease are the most common causes of kidney cysts in the neonatal population. This review highlights the most common kidney cystic diseases during the neonatal period and a rare clinical case of HNF1B-associated disease.